2016
DOI: 10.1371/journal.pone.0161039
|View full text |Cite
|
Sign up to set email alerts
|

Serum-Based Quantification of MYCN Gene Amplification in Young Patients with Neuroblastoma: Potential Utility as a Surrogate Biomarker for Neuroblastoma

Abstract: We previously developed a method for determining MYCN gene amplification status using cell-free DNA fragments released from cancer cells into the blood of patients with neuroblastoma (NB). Here, we analyzed the relationship between MYCN amplification (MNA) status and neuroblastoma prognosis. We screened serum samples from 151 patients with NB for MNA, using real-time quantitative PCR, and compared the results with MYCN status determined using paired tumor samples. We additionally investigated whether MNA statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 30 publications
3
30
0
Order By: Relevance
“…When cutoff of serum MYCN/NAGK ratio was set at 10, the sensitivity and specificity to distinguish MYCN amplification were both 100%. Furthermore, patients with MYCN/NAGK ratio beyond 5 had worse overall survival, particularly in those less than 18 months of age [37]. After surgery or neoadjuvant chemotherapy in NB, plasma copy numbers of MYCN were significantly decreased [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When cutoff of serum MYCN/NAGK ratio was set at 10, the sensitivity and specificity to distinguish MYCN amplification were both 100%. Furthermore, patients with MYCN/NAGK ratio beyond 5 had worse overall survival, particularly in those less than 18 months of age [37]. After surgery or neoadjuvant chemotherapy in NB, plasma copy numbers of MYCN were significantly decreased [35].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, plasma cell-free DNA (cfDNA) quantification is emerging as a promising and noninvasive method to predict tumor burden in NB [29][30][31]. More importantly, serum or plasma MYCN copy number quantification by real-time quantitative polymerase chain reaction (qPCR) was used to predict amplified MYCN of tumor in NB, at different cutoff value [32][33][34][35][36][37]. Remarkably, less work is done with plasma DNA and more clinical tests are needed.…”
Section: Introductionmentioning
confidence: 99%
“…This test may help select patients for anti-EGFRvIII therapy and monitor response to treatment [108]. In patients with neuroblastoma, serum MYCN amplification (real-time quantitative PCR, sensitivity 86%, specificity 95% compared with tissue analysis) was associated with OS, suggesting that it may help select treatment prior to tumor biopsy, particularly for patients younger than 18 months whose risk assessment and treatment depend on MYCN amplification status [109]. In patients with glioma, the IDH1 R132H mutation was identified in plasma with a specificity of 100% and sensitivity related to the tumor volume and contrast enhancement, suggesting that it may help in the diagnosis of patients not amenable to biopsy [110].…”
Section: Brain Tumorsmentioning
confidence: 99%
“…The determination of serum MYCN DNA sequences by real‐time quantitative PCR is sensitive as a diagnostic tool. Furthermore, serial detection of the serum MYCN copy number has monitoring and predictive value in terms of disease progression or relapse during treatment and follow‐up 25 …”
Section: Genomic Alterationsmentioning
confidence: 99%
“…While previous reports suggested that determination of the serum MYCN copy number by real‐time quantitative PCR has the potential to supplant core biopsy for testing of this marker, this method has lower sensitivity for patients with NB of INSS stages 1 and 2 25,29 . The levels of ctDNA are higher for patients with metastatic diseases than for patients with localized tumors and this may be associated with the tumor burden and metabolism, as well as the standardization of procedures.…”
Section: Genomic Alterationsmentioning
confidence: 99%